Premodern Experience of the Natural World in Translation - Krause, Katja; Auxent, Maria; Weil, Dror (Taylor & Francis, 2023)
This innovative collection showcases the importance of the relationship between translation and experience in premodern science, bringing together an interdisciplinary group of scholars to offer a nuanced understanding of knowledge transfer across premodern time and space. The volume considers experience as a tool and object of science in the premodern world, using this idea as a jumping-off point from which to view translation as a process of interaction between diff erent epistemic domains. The book is structured around four dimensions of translation-between terms within and across languages; across sciences and scientific norms; between verbal and visual systems; and through the expertise of practitioners and translators-which raise key questions on what constituted experience of the natural world in the premodern area and the impact of translation processes and agents in shaping experience. Providing a wide-ranging global account of historical studies on the travel and translation of experience in the premodern world, this book will be of interest to scholars in history, the history of translation, and the history and philosophy of science.